On the continuum of evolution: a putative new hybrid speciation event in Opuntia (Cactaceae) between a native and an introduced species in southern South America. Issue 8 (17th November 2021) - Köhler, Matias; Oakley, Luis J.; Font, Fabián; Peñas, M. Laura Las; Majure, Lucas C.
Abstract : Hybridization plays a fundamental role in plant evolution and diversification, promoting gene flow, morphological novelties, and plant speciation. Here, we integrated fieldwork, collections-based research, morphological observations, molecular systematics, and cytogenetic data to investigate the identity of a previously unidentified taxon of Opuntia (the prickly pear cacti) observed in the north-east region of Argentina, southern South America. Our analyses revealed a cytonuclear phylogenetic discordance among nuclear and plastid genomes, as well as a polyploid nature of the studied taxon. Combining our molecular phylogenetic and cytogenetic analyses with morphological observations, we suggest that hybridization events between the native Opuntia rioplatensis and the North American introduced species, O. ficus-indica, likely produced the taxon here described as O. × cristalensis. Opuntia is the most widespread genus of Cactaceae, and many species have been introduced worldwide for an array of different purposes. Our report proposes the putative first hybridization event in Opuntia between a North American species with a southern South American lineage, which may shed light on more complex evolutionary scenarios, speciation within the group, and the impacts of species introduction.